Peningkatan Kinerja Usaha Fotokopi Melalui Optimalisasi Prinsip Ekonomi Syariah - M. Khoriul Muttaqin; Nursamsi Nursamsi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines the application of sharia economic principles in the photocopying and office stationery (ATK) business in the pesantren environment, focusing on business performance that is not only financially profitable but also has a positive impact on society and the environment. Using a qualitative approach, this study analyzes current business practices as well as strategies that can be applied to integrate sharia values, such as the prohibition of riba, gharar, and maysir. The findings of the study show that the application of sharia economics can improve business performance through capacity building, cooperation with Islamic financial institutions, and technology adoption.